Pengembangan Media Video Interaktif pada Kemampuan Bahasa Anak Usia Dini TK IB 71 Sialang Gaun - Oqtika, Yulia; Salahudin, Amar; Ningsih, Sri Yunimar (Jurnal Ilmiah Dikdaya, 2025)
Education is defined as a process related to human potential (ability, capacity) that is easily influenced by habits, which are then perfected with good habits, through media that are arranged and managed in such a way by humans to help others or themselves in achieving the goals set. In Indonesia itself, a 12-year compulsory education program has been implemented, starting with Kindergarten (TK), Elementary School (SD), Junior High School (SMP), and Senior High School (SMA). This shows that the early education taken by a person will be the basis for the emergence of positive social attitudes and growth regarding a knowledge competency.      Character building and the formation of social attitudes that are easy to do when the child is still in Kindergarten The childhood growth period is the "Golden Age", the Golden Age is the age of children when they are zero to six years old, this age is at the best development for the child's physical and brain. Early Childhood Education is an effort to foster children from birth to the age of six years carried out through the provision of educational stimulation to help physical and spiritual growth and development so that children are ready to enter further education. Education has a very important meaning or significance in preparing children to build their future.     Early Childhood Education is a form of education that focuses on the direction of growth and six developments, namely: moral and religious development, physical development, namely gross and fine motor coordination, intelligence or cognitive, namely thinking power and creativity, social emotional, namely attitudes and emotions, language and communication, in accordance with the uniqueness and stages of development based on the age group that has been passed by the child.  Becoming a teacher for early childhood in presenting information to early childhood must use media so that what is to be conveyed to children is easy for children to understand and it is hoped that there will be behavioral development in the form of abilities, attitudes and skills. In modern times as we feel now, the existence and role of information technology in the education system has ushered in a new era of development in the world of education, but this development has not been balanced by an increase in human resources which can later determine the success of the goals of the Indonesian education world. New technologies often gather a lot of excitement and impact. Early childhood feels happy and interested when learning if the learning media uses a computer/laptop, children will prefer learning that is made and equipped with animations, images, music and videos.